A Comparative Study of the User Interaction Behavior and Experience in a Home-Oriented Multi-User Interface (MUI) During Family Collaborative Cooking - Mengcai Zhou; Minglun Li; Kenta Ono; Makoto Watanabe (Future Internet)
This study sought to ascertain the necessity of crafting specialized multi-user interfaces for scenarios involving multiple users and to provide guidance for the design of multi-user human–computer interactions by identifying the disparities in the interaction behavior and user experience when employing a conventional one-user interface (OUI) recipe versus a multi-user interface (MUI) recipe in the context of family collaborative cooking. To address this objective, this study employed a before-and-after comparison approach. Subsequently, adult users submitted self-assessments of their experiences using the OUI and MUI. The evaluation tools included a user experience survey questionnaire and a Likert seven-point scale, including aspects such as visual confirmation, content, operation, and satisfaction. Post-experiment interviews were also conducted with family members. The MUI exhibited greater effectiveness in terms of visual confirmation, with the “layout” assuming a role analogous to that of “text” in facilitating visual confirmation. Moreover, the operation of the MUI was found to be somewhat enjoyable. Nevertheless, no significant disparities were observed between the OUI group and the MUI group concerning content readability and most operational aspects. Furthermore, the users described their satisfaction with the MUI to be superior to that of the OUI, offering fun, convenience, and a clear appearance. Findings from my research clearly demonstrate that it is both valuable and essential to design a dedicated MUI.